Implementation of Global Governance on School Feeding in The Policy of School Children Nutrition Program (Pro-GAS) in 2018 in Kulon Progo Regency - Intan Annisa Putri; Andriko Sandria (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Indonesian government initiating a program called the School Child Nutrition Program (PROGAS) in 2016 as respon to FAO’s School Feeding program in NTT and Papua 2012 which successfully improve nutrition and eduction there. The purpose of this paper is to asses the PROGAS in Kulon Progo in specific using globa governance framework on school feeding. This study used a descriptive qualitative approach with data collection techniques in the form of literature studies. Data analysis consists of the stages of collecting data, categorizing data, presenting data, and drawing conclusions. The results of this study indicate that the FAO regime influences the decision-making of school food delivery programs starting from School Child Supplement Program (PMT-AS) in 1991 to the School Child Nutrition Program (PROGAS) in 2016. Implementation of PROGAS in Kulon Progo, the government has followed the principles and standards imposed by global governance such as the use of local products, community participation, and targeting based on needs. However, several other standards such as sustainability, funding, and a strong institutional structure are still the big task of the Indonesian government to realize a sustainable and long-term program. Keywords: Food and Agriculture Organization (FAO), Hunger and Malnutrition, International Regime, School Child Nutrition Program (PROGAS)